Baclofen modulates cardiovascular responses to appetitive cues in treatment‐seeking alcohol use disorder individuals. (11th February 2020) - Logge, Warren B.; Baillie, Andrew J.; Haber, Paul S.; Morley, Kirsten C.
Abstract: Objective: To assess whether baclofen‐treated alcohol dependent participants show different subjective and psychophysiological responses to appetitive cues during an alcohol cue reactivity task compared to placebo, and whether these responses are associated with prospective drinking outcomes. Methods: Forty‐two alcohol dependent participants (placebo: n = 12, low‐dose baclofen [30 mg/day] n = 18, high‐dose baclofen [75 mg/day]: n = 12) completed an alcohol cue reactivity task, whereby water and alcohol beverage cues were presented, with subsequent recovery periods, and subjective alcohol craving and psychophysiological indices (skin conductance; cardiovascular measures: heart rate, high‐frequency heart rate variability) were recorded. Results: High‐dose baclofen‐treated participants showed both overall cue reactivity to water and alcohol cues and greater recovery effects during recovery periods, revealed by high‐frequency heart rate variability, when compared to low‐dose‐ and placebo‐treated participants. There were no medication effects on subjective craving. In high‐dose baclofen participants only, there was a predictive effect of lower baseline heart rate variability and fewer post‐test percentage of heavy drinking days. Conclusion: There was a dose‐specific rescuing effect of high‐dose baclofen on the dynamic modulation of cardiovascular responses to eliciting cues. Investigation of treatment responses using psychophysiological techniques may elucidate baclofen's mechanisms of action, and identify subgroups amenable to treatment.